Key items for reports of primary care research: an international Delphi study. Issue 12 (19th December 2022) - Sturgiss, Elizabeth Ann; Prathivadi, Pallavi; Phillips, William R; Moriarty, Frank; Lucassen, Peter L B J; van der Wouden, Johannes C; Glasziou, Paul; Olde Hartman, Tim C; Orkin, Aaron; Reeve, Joanne; Russell, Grant; van Weel, Chris
Abstract : Objective: Reporting guidelines can improve dissemination and application of findings and help avoid research waste. Recent studies reveal opportunities to improve primary care (PC) reporting. Despite increasing numbers of guidelines, none exists for PC research. This study aims to prioritise candidate reporting items to inform a reporting guideline for PC research. Design: Delphi study conducted by the Consensus Reporting Items for Studies in Primary Care (CRISP) Working Group. Setting: International online survey. Participants: Interdisciplinary PC researchers and research users. Main outcome measures: We drew potential reporting items from literature review and a series of international, interdisciplinary surveys. Using an anonymous, online survey, we asked participants to vote on and whether each candidate item should be included, required or recommended in a PC research reporting guideline. Items advanced to the next Delphi round if they received>50% votes to include. Analysis used descriptive statistics plus synthesis of free-text responses. Results: 98/116 respondents completed round 1 (84% response rate) and 89/98 completed round 2 (91%). Respondents included a variety of healthcare professions, research roles, levels of experience and all five world regions. Round 1 presented 29 potential items, and 25 moved into round 2 after rewording and combining items and adding 2 new items. A majority of round 2 respondents voted to include 23 items (90%–100% for 11 items, 80%–89% for 3 items, 70%–79% for 3 items, 60%–69% for 3 items and 50%–59% for 3 items). Conclusion: Our Delphi study identified items to guide the reporting of PC research that has broad endorsement from the community of producers and users of PC research. We will now use these results to inform the final development of the CRISP guidance for reporting PC research.